Falling into Glăveanu’s Gap: A lyric essay searching for resilience through creativity - Noble, Helen; Cole, Beverly (European Journal for Qualitative Research in Psychotherapy, 2024)
This paper is in two parts comprising a literature review and a creative, non-fiction, lyric essay format to explore interplay between ambivalent emotions, creativity, and resilience. The context is my own state affect between client sessions, as a psychotherapist and researcher. The lyric essay, “Falling into Glăveanu’s Gap,” that comprises the second part of this paper covers a period of great disquiet in my personal and professional life, when adverse life experiences impacted my research, and, as such, formed an integral part of the research itself. My self-search heuristic exploration forms part of a larger, doctoral enquiry into the interplay between ambivalence, creativity, and resilience amongst therapists, examining whether those engaged in creativity experience a greater sense of resilience. Resilience is the antithesis of burnout, a condition which disproportionately affects practicing therapists. This research argues that therapist education, training and continuing professional development provision, would benefit from a stronger focus on therapist emotion and affect, outside of the therapy room. Opportunities for engagement with creativity are recommended to aid the development of therapist resilience and to combat therapist burn-out.